Kecepatan dan kekuatan atlet bela diri: Apakah plyometrics mempengaruhi pemulihan aktif-pasif? - Kurniawan, Candra; Hadi, Hadi; Novriansyah, Novriansyah (Universitas Nusantara PGRI Kediri, 2022)
In addition to good physical and psychological conditions, recovery is another important component that athletes must meet to support success in the field. This study aims to determine the effect of active and passive recovery on plyometric exercises on speed and power. The type used in this study is quasi-experimental. The sample of this research is 44 athletes from Lampung Province who will compete for Pekan Olahraga Nasional (PON) 2021 Papua. The plyometric exercises applied are plyometric exercises (multiple hops and jump variations). After doing the plyometric exercises, active and passive recovery is applied. The speed research instrument is the 30 m sprint test for power using a vertical jump. Analysis of the data used: paired test analysis and independent sample test. The results obtained are that plyometric exercises on active and passive recovery affect athletes' speed and power abilities. Although it affects performance, in the effectiveness test, the speed of active recovery is better than passive recovery. As for power, both of them do not have the level of effectiveness between passive and active recovery. The study's results are expected to be a reference to be included in the training program using the plyometric model with active and passive recovery to support the success of the Lampung Province athletes in 2021.